Seismic Analysis of Isolated Continuous Bridge considering Influence of Seawater and Site Condition - Baokui Chen; Yujie Du; Yan Shi; Li Fan (Shock and Vibration)
The effects of seawater and site conditions on the seismic response of the isolated continuous girder bridge are evaluated in this study. The seawater-muddy soil-isolated bridge coupling model is built in the dynamic analysis software ADINA, and the external seismic wave input is realized by the seismic wave motion analysis program. The influences of seawater and muddy soil on the seismic response of isolated continuous girder bridges are determined by comparing different offshore site models. The results indicated that the seawater and the muddy soil magnify the displacement of the seabed. The existence of seawater increases the longitudinal relative displacement of piers by 20%–40% but has limited influence on the bending moment and shear force of piers. The muddy soil can increase the longitudinal relative displacement and internal force of the piers remarkably. Moreover, the displacement of bridge bearings increases significantly under the combined influence of muddy soil and seawater. In the seawater-muddy soil-isolated bridge coupling model, the seawater and site condition can influence the seismic performance of sea-crossing bridges obviously.